2019
DOI: 10.1177/0038026119837147
|View full text |Cite
|
Sign up to set email alerts
|

Hitting the ‘glass wall’: Investigating everyday ageism in the advertising industry

Abstract: This article contributes to the growing research into the structural inequalities characterising the cultural industries by investigating the lived experience of older cultural workers. By drawing on 22 in-depth interviews with experienced advertising creatives it explores how ageism manifests itself in the creative departments of advertising agencies and how older creatives negotiate their professional identities in response to ageist representations, discourses and practices. By focusing on one of the so far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Geriatric crisis center, cosmetic surgery clinic, office of ageing." In-depth interviews also found that ageism existed in the advertising industry, with older workers perceived by young workers as "dead wood" [39]. Overall, the results are remarkably similar: Negative stereotypes are highly prevalent, compared to positive stereotypes.…”
Section: Conceptual Framework and Measurement Of Age Stereotypesmentioning
confidence: 81%
“…Geriatric crisis center, cosmetic surgery clinic, office of ageing." In-depth interviews also found that ageism existed in the advertising industry, with older workers perceived by young workers as "dead wood" [39]. Overall, the results are remarkably similar: Negative stereotypes are highly prevalent, compared to positive stereotypes.…”
Section: Conceptual Framework and Measurement Of Age Stereotypesmentioning
confidence: 81%
“…In the work-life accounts, research participants often explain ageism with reference to their personal attributes, such as slowing bodies (Bowman et al, 2017), decreased work ability (McMullin & Marshall, 2001), increased health problems (Crăciun, Rashe, Flick, & Hirseland, 2018), and low skills and ability to learn new things (Crăciun et al, 2018;McMullin & Marshall, 2001). Beyond these negative attributes, research participants have explained ageism in relation to their over qualification and the expensiveness that comes with experience (Brodmerkel & Barker, 2019;Noonan, 2005) or expertise that enables them to resist management's authorities (Bowman et al, 2017;Moore, 2009). Working life experiences of ageism are not only related to workers' age but also the age of the clients that professionals encounter.…”
Section: Subjects and Intersectionalitymentioning
confidence: 99%
“…Aging as a Hindering Process. Numerous papers claim that ageism derives from the social construction of aging as a hindering process and the obsession of our society to be ageless and aspire for perpetual youthfulness and beauty (Brodmerkel & Barker, 2019;Laliberte-Rudman, 2015a;Laliberte-Rudman & Molke, 2009;Romaioli & Contarello, 2019;Spedale, 2019;Spedale et al, 2014). Spedale et al's (2014) analysis of an age discrimination case-law report from a UK tribunal showed that youth ideologies are reified in the workplace and used to justify rejuvenation discourses and practices.…”
Section: Social Construction Of Age and Ageist Ideologies Discourses And Ideologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the advertising sector constantly seeking “fresh” ideas, age is a barrier manifested on the body, experienced as negative, and leading to feelings of insecurity as well as to glass ceilings for both men and women (Brodmerkel & Barker, 2019), often constituting a worse form of discrimination than gender or race (Coffee, 2016). Global statistics indicate that less than 10% of employees are over 50 years old in advertising (Brodmerkel & Barker, 2019) and older creative workers are often pushed towards self‐employment (Hennekam, 2015). It is worth noting that in the study of Brodmerkel and Barker (2019) the sample comprised 18 men and only four women, out of which three were self‐employed.…”
Section: Introductionmentioning
confidence: 99%